ROLE OF POTASSIUM IN PHYSIOLOGICAL FUNCTIONS OF SPRING MAIZE (Zea mays L.) GROWN UNDER DROUGHT STRESS - M. Aslam M. S. I. Zamir; I. Afzal; M. Amin (Journal of Animal and Plant Sciences, 2014)
Drought stress leaves deleterious effects on growth of maize plant while potassium plays an important role in reducing such deleterious effects. To study the role of potassium on maize plant grown under drought stress an experiment was conducted at Postgraduate Agricultural Research Station, Faisalabad, Pakistan. Maize hybrids 32-F-10 (drought tolerant) and YH-1898 (drought sensitive) were grown on February 25, 2010 and in next year on February 21, 2011. Drought treatments were imposed on growth stages such as; no drought, at five-leaf stage, at ten-leaf stage, at anthesis and at grain formation while two potassium treatments were such as; no potassium and 100 mg/kg of soil application. The design of experiment was RCBD with split-split arrangement. The field capacity was determined by gravimetric method while application of water in drought treatment was maintained by using a formula. It was found that application of potassium had significant effects on relative water contents, leaf water potential, turgor potential, photosynthetic rate, transpiration rate, grain weight per cob, biological yield and grain yield during both the years 2010 and 2011 when drought was imposed at critical growth stages. However, potassium effect on osmotic potential was only significant during 2010. Thus, potassium could be helpful in drought stress mitigation as well to improve produce quality.
Keywords: Potassium; water relation; gas exchange; spring maize and water deficit